Investigation of food poisoning on distribution of takjil in Tempel Sleman - Ghilari, Yampa Eksa Daidella; Sriadi, Yoshua Natanael; Dharmawidjaja, Isa; Indriani, Citra (BKM Public Health and Community Medicine, 2021)
Objective: On 4th May 2021, Sleman District Health Office (DHO) received suspect food poisoning with 28 cases after eating packaged takjil were distributed on 2nd May 2021. The investigation was initiated to confirm the outbreak risk factor for control measures. Method: This investigation uses a cohort retrospective design. The case was the person who have one or more following symptoms diarrhea, abdominal pain, weakness, and fever after eating takjil on 2nd May 2021 in Krasakan village. The interview was conducted using standard questionnaires at-risk population and food handlers. The environmental observation was done in the kitchen of catering. Food and biological sample were sent to the laboratory. Results: There were 28 cases from 60 people who ate (Attack Rate: 46%) with dominant symptoms: diarrhea, abdominal pain, and weakness (100%). The incubation period was 7-33 hours with a median of 10 hours. Oseng tempe was food with the highest risk (RR= 6.09, CI= 1,5 -24,8). The environmental investigation found that contamination might have occurred as a result of poor processing practices such as improper food storage was potential risk contamination. We suspected Bacillus cereus as the main pathogen according to incubation period and mode transmission, but the laboratory showed different results, it can happen because the sample was sent 2x24 hours so the result was not adequate. Conclusion: There was a food poisoning outbreak from the distribution of takjil on 2nd May 2021 in Krasakan Village, caused by oseng tempe contaminated with Bacillus cereus. Contamination occurs due to improper cooking and storage. Implementation and training standard health and safety food handling need to be done for food caterer by District Health Office.